2010
DOI: 10.1016/j.stem.2010.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Nitric Oxide Activates Notch Signaling and Promotes Stem-like Character in PDGF-Induced Glioma Cells

Abstract: SUMMARY eNOS expression is elevated in human glioblastomas and correlated with increased tumor growth and aggressive character. We investigated the potential role of nitric oxide (NO) activity in the perivascular niche (PVN) using a genetic engineered mouse model of PDGF-induced gliomas. eNOS expression is highly elevated in tumor vascular endothelium adjacent to perivascular glioma cells expressing Nestin, Notch, and the NO receptor, sGC. In addition, the NO/cGMP/PKG pathway drives Notch signaling in PDGF-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
409
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 490 publications
(425 citation statements)
references
References 40 publications
12
409
0
4
Order By: Relevance
“…Microglia are known in other pathological conditions to increase endothelial cell migration and proliferation as well as to stimulate reactive gliosis. In this manner, microgliainduced neoangiogenesis might create a supportive niche for cancer stem cells, as has been reported for highgrade gliomas (Ludwig et al, 2000;Ren et al, 2004;Calabrese et al, 2007;Charles et al, 2010), and account for the highly vascular nature of these otherwise relatively benign tumors. Although it is not known what impact Nf1 heterozygosity has on brain endothelial cell function, Nf1 þ /À aortic endothelial cells exhibit increased motility and proliferation and likely participate in establishing a permissive environment for peripheral nerve sheath tumors .…”
Section: Resultsmentioning
confidence: 65%
“…Microglia are known in other pathological conditions to increase endothelial cell migration and proliferation as well as to stimulate reactive gliosis. In this manner, microgliainduced neoangiogenesis might create a supportive niche for cancer stem cells, as has been reported for highgrade gliomas (Ludwig et al, 2000;Ren et al, 2004;Calabrese et al, 2007;Charles et al, 2010), and account for the highly vascular nature of these otherwise relatively benign tumors. Although it is not known what impact Nf1 heterozygosity has on brain endothelial cell function, Nf1 þ /À aortic endothelial cells exhibit increased motility and proliferation and likely participate in establishing a permissive environment for peripheral nerve sheath tumors .…”
Section: Resultsmentioning
confidence: 65%
“…Recently, Eyler et al 54 found that proliferation of glioma stem-like cells is facilitated by nitrogen oxide (NO), whereas the increase of NO had no effect on cell growth of normal neural stem cells. The role of NO in facilitating glioma cell growth was further supported by Charles et al, 55 in which they found that NO activates Notch signaling and promotes glioma stem-like cell population in vivo. In our study, we found that Notch signaling is activated by JNK signaling.…”
Section: Discussionmentioning
confidence: 85%
“…Tumor endothelial cells, which highly express eNOS, the enzyme required for nitric oxide synthesis in the endothelium, lies adjacent to nestin-expressing BTSCs associated with the PVN. Activated Notch signaling by nitric oxide in BTSCs was shown to accelerate tumor progression (Charles et al, 2010). This finding identifies potentially new targets for the rational design of drugs against the PVN.…”
Section: Brain Tumor-cell Endothelial-cell Signalingmentioning
confidence: 98%
“…NO activates notch signaling in a population of BTSCs, to enhance their self-renewal characteristics in vitro and their tumorigenic capacities in vivo. Further, eNOS, an enzyme that synthesizes NO from the vascular endothelium, is elevated in the platelet-derived growth factor (PDGF)-subset of gliomas and suppression of eNOS activity, which corresponded to a decrease in notch signaling in these tumors, prolonged survival of tumor bearing mice (Charles et al, 2010). It remains to be determined whether maintenance of cancer stem cell populations by NO signaling from the tumor endothelium is conserved across other brain tumor subtypes and other types of cancers.…”
Section: Brain Tumor Stem-like Cellsmentioning
confidence: 99%